2015
DOI: 10.5539/ies.v8n5p101
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Productivity Practical Management Model at Automotive Mechanical Technology Skill Program in Semarang Vocational Schools, Indonesia

Abstract: The purpose of this research is to develop automotive Mechanical Technology Skill Program (TMO) in Vocational School. The Research and Development (R&D) object was done in SMK 1, 4 and 7 Semarang, Indonesia. The result was achieved productivity Practical Management Final Model at TMO skill Program in Vocational school named momanticproter. Momanticproter is an advanced study of functional planning management, action, and evaluation in man, money, method, material and minute aspects to productivity practical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The learning process was carried out in these stages; (1) group learning made the vocational teacher candidates felt more confident and comfortable; (2) the stages of observing strengthened them to be more motivated and increase their curiosity; (3) the stage of experimenting / gathering information made vocational teacher candidates more comfortable to gather information that can be performed together, exchanged ideas and experiences; (4) stages of associating, adding breadth and depth to information by processing information by seeking solutions from various sources; (5) communication stage, vocational teacher candidates were trained to convey the results of learning by reporting and presenting to the class. This is in line with the integrated productive practice management model (momantikproter) developed by Hadromi (2015). Hadromi (2015) argued that the application of momantikproter provides opportunities for teaching staff; participants learned to have an integral understanding of practice material, and have implications for increasing motivation to optimize their potential.…”
Section: Learning Implementationmentioning
confidence: 59%
“…The learning process was carried out in these stages; (1) group learning made the vocational teacher candidates felt more confident and comfortable; (2) the stages of observing strengthened them to be more motivated and increase their curiosity; (3) the stage of experimenting / gathering information made vocational teacher candidates more comfortable to gather information that can be performed together, exchanged ideas and experiences; (4) stages of associating, adding breadth and depth to information by processing information by seeking solutions from various sources; (5) communication stage, vocational teacher candidates were trained to convey the results of learning by reporting and presenting to the class. This is in line with the integrated productive practice management model (momantikproter) developed by Hadromi (2015). Hadromi (2015) argued that the application of momantikproter provides opportunities for teaching staff; participants learned to have an integral understanding of practice material, and have implications for increasing motivation to optimize their potential.…”
Section: Learning Implementationmentioning
confidence: 59%
“…Tsai and Liu (2015) revealed that collegial school management, as well as responsibilities among teachers, influence communication and interpersonal skills (Abulibdeh, 2013). The significant positive relationship exists between academic students' skills and collegial school management, as well as employability skills (Harrris, 2013;Kraebber and Greenan, 2012;Hadromi & Soesanto, 2015).…”
Section: Collegial School Management and Students' Life Skillsmentioning
confidence: 99%
“…Confirmed by Hadromi (2016) [12] management started from needing analyzing, planning, organizing, supervising, and evaluating Table 5 up to 8 illustrates the performance management of community service and empowerment in 792 2016 in Kandri village, Semarang, Indonesia. Specifically, this study focused on economic empowerment of rural communities through farmers" empowerment using community learning center in Kandri village as Argoecotourism.…”
Section: Results and Discussion:-mentioning
confidence: 90%